Vanadium-Catalyzed Selective Oxidative Homocoupling of Alkenyl Phenols to Synthesize Lignan Analogs - Neuhaus, William C. (ACS Catal, 2019)
The oxidative homocoupling of para-alkenyl phenols and subsequent trapping of the resulting quinone methide with a variety of oxygen and nitrogen nucleophiles was achieved. Both β-β and β-O coupling isomers can be synthesized via either C-C coupling and two nucleophilic additions of one water molecule (β-β isomer) or C-O coupling followed by one nucleophilic addition of a water molecule (β-O isomer), respectively. Selectivity between these outcomes was achieved by leveraging understanding of the mechanism. Specifically, a qualitative predictive model for the selectivity of the coupling was formulated based on catalyst electronics, solvent polarity, and concentration.